Nursing Education and Soft Skills Strengthening in Holistic Nursing Services - Hardjito S. Darmojo; M. Adila Rossa; Al-Bahra (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2021)
Nursing education plays a strategic role in developing professionally competent nurses capable of providing holistic nursing services. One of the main challenges in nursing education is strengthening soft skills, including communication, empathy, teamwork, problem-solving, and clinical decision-making. This study aims to analyze the relationship between nursing education and strengthening soft skills in holistic nursing services. This study used a quantitative design with a cross-sectional approach. The study sample consisted of 110 respondents, consisting of final-year nursing students and novice clinical nurses, selected using a proportionate stratified random sampling technique. Data were collected using a structured questionnaire based on a Likert scale that had been tested for validity and reliability. Data analysis included univariate analysis, bivariate analysis using the Pearson correlation test, and multivariate analysis with simple linear regression. The results showed that the majority of respondents rated nursing education as high, and the level of respondents' soft skills was also in the good category. There was a strong and significant positive relationship between nursing education and strengthening soft skills (r = 0.621; p < 0.001). Nursing education contributed 38.6% to the variation in soft skills in holistic nursing services. This study concludes that integrated nursing education with a holistic approach and active learning strategies plays a crucial role in developing nurses' soft skills. These findings are expected to form the basis for developing a nursing education curriculum that balances technical and non-technical competencies.